GAMBARAN HISTOPATOLOGIK LAMBUNG TIKUS WISTAR SETELAH DIINDUKSI DENGAN ASPIRIN - Lintong, Poppy M; Loho, Lily L.; Anggran, Herman (JURNAL BIOMEDIK : JBM, 2013)
Abstract: Aspirin is one of the non-steroid-anti-inflammatory drugs. Its pharmacodynamic effects are as an analgesic, antipyretic, anti-inflammatory, anti-thrombotic, and uricosuric agent. The side effects of aspirin are on the respiratory tract, the gastrointestinal tract, blood, metabolic processes, endocrine functions, pregnancy, hypersensitivity, and drug interaction. The purpose of this study was to evaluate the macroscopic and microscopic features of wistar rat stomachs after the administration of aspirin. This was an experimental study, using nine wistar rats divided into three groups equally. Group I, the control group, was given a food pellet only. Group II was given the pellet, added with aspirin 21 mg daily for 10 days. Group I and Group II were terminated on day 11. Group III was given the pellet, added with aspirin 21 mg/day for 10 days, and was terminated on day 14. All the wistar rat stomachs were examined macroscopically and microscopically. The results showed that the control group had a macroscopically normal stomach architecture, and the mucosa layers and rugae were intact and looked pinkish white. The groups treated with aspirin still showed normal stomach architecture, and the mucosa layers and rugae were intact but looked more palid than that of the control group. Microscopically, the stomach walls of the control group were normal, but groups treated with aspirin for 10 days revealed edema of the lamina propria, dilatation of capillaries; and predominantly neutrophilic infiltration in the lamina propria. Ceasing of aspirin administration showed a resolution of the inflammatory process, marked by diminished infiltration of PMN cells and tisuue edema. Conclusion: Aspirin treatment of 21 mg a day for 10 days revealed histopathologically acute gastritis of the wistar rat stomach walls. The inflammatory reaction was diminished after the cessation of aspirin. Keywords: aspirin, histopathology, stomach.   Abstrak: Aspirin tergolong obat anti-inflamasi non-steroid (AINS) yang secara farmakodinamika mempunyai efek analgesik, anti-piretik, anti-inflamasi, anti-trombotik, dan urikosurik, namun mempunyai efek samping pada saluran  cerna terutama lambung. Penelitian ini bertujuan untuk mendapatkan gambaran histopatologik (makroskopik dan mikroskopik) lambung tikus Wistar setelah pemberian aspirin. Penelitian ini bersifat eksperimental dengan menggunakan sampel sembilan ekor tikus Wistar yang dibagi atas tiga kelompok. Kelompok I (kontrol) terdiri dari tiga ekor tikus yang diberi pelet biasa dan air minum. Kelompok II terdiri dari tiga ekor tikus yang diberi pelet biasa, air minum, dan aspirin dosis 21 mg/hari  selama 10 hari. Pada hari ke-11 kelompok I dan II diterminasi. Kelompok III terdiri dari tiga ekor tikus yang diberikan pelet biasa, air minum, dan aspirin dosis 21 mg/hari selama 10 hari, kemudian aspirin dihentikan dan tikus diterminasi pada hari ke-14. Setelah diterminasi, kelompok I-III diotopsi, diambil organ lambungnya, kemudian dilakukan pemeriksaan histopatologik. Hasil penelitian memperlihatkan makroskopik mukosa lambung tampak lebih pucat sedangkan mikroskopik menunjukkan tanda-tanda radang akut. Penghentian pemberian aspirin diikuti dengan resolusi reaksi inflamasi yang ditandai oleh penurunan infiltrasi sel-sel radang PMN dan edema jaringan. Sinpulan: Pemberian aspirin 21 mg/hari selama 10 hari mengakibatkan terjadinya gambaran histopatologik gastritis akut pada lambung tikus Wistar. Reaksi inflamasi menurun setelah penghentian pemberian aspirin. Kata kunci: aspirin, histopatologi, lambung.